Zintegrowane centrum komunikacji w Zielonej Górze - koncepcja rewitalizacji terenu przydworcowego = Zielona Góra communication center - the concept of bus and train station revitalisation - Kostecki, Jakub; Tesz, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Stops, stations, and then the railway station in Zielona Góra, historically have been located on the outskirts of built-up area. This rule was retained in the construction of the railway line and station in the 2nd half of the XIXth century ? this line was built approx. 1 km north of City Hall and approx. 600 m from the boundaries of urban built-up area. Near the railway station a large industrial plants, depots and service plants were built.
Keywords: dworzec kolejowy; zagospodarowanie terenu; rewitalizacja; railway station; bus station; land use; revitalisation